What Is Influencer Marketing and How Does It Target Children? A Review and Direction for Future Research - De Veirman, Marijke; Hudders, Liselot; Nelson, Michelle R. (Frontiers in Psychology, 2019)
Children nowadays spend many hours online watching YouTube videos in which their favorite vloggers are playing games, unboxing toys, reviewing products, making jokes or just going about their daily activities. These vloggers regularly post attractive and entertaining content in the hope of building a large follower base. Although many of these vloggers are adults, the number of child vloggers is flourishing. The famous child vlogger Ryan of Ryan’s Toy Review, for instance, has more than 19 million viewers and he is (at age seven) a social media influencer. The popularity of these vloggers incited advertisers to include them as a new marketing communication tool, also referred to as influencer marketing, in their marketing strategy. Accordingly, many influential vloggers now receive free products from brands in return for a mention in one of their videos and their other social media (e.g., TikTok or Instagram) and some are even paid to create a sponsored post or video and distribute it to their followers. This sponsored content appears to be highly influential and may affect young children’s brand preferences. Given the limited advertising literacy skills (i.e., knowledge of advertising and skills to critically reflect on this advertising) of children under age twelve, they are a vulnerable target group when it comes to persuasion. Therefore, caution is needed when implementing this marketing tactic to target them. However, research on how influencer marketing affects young children (under twelve) is scarce and it is unclear how these young children can be empowered to critically cope with this fairly new form of persuasion. This paper therefore aims to shed light on why and how social media influencers have persuasive power over their young followers. The paper starts with providing insights into how and why social media influencers became a new source in advertising. We then discuss the few studies that have been conducted on influencer marketing among young children (under twelve), based on a systematic literature review, and take these findings to formulate societal and policy implications and develop a future research agenda.